Financial Sector Assessment : Uruguay - World Bank (Washington, DC, 2013)
Uruguay suffered a severe banking and currency crisis in 2002 from the spillover of Argentina's crisis. The crisis highlighted important underlying weaknesses of the Uruguayan financial sector, many of which were already well known. This Financial Sector Assessment summarizes the findings of a joint International Monetary Fund/World Bank Financial Sector Assessment Program (FSAP) team that visited Montevideo in October 2005 and January-February 2006. The purpose of the assessment was to help the authorities identify financial system strengths and weaknesses with a view to implementing an action plan to increase the system's contribution to economic development. The FSAP assessment is based on information provided by the authorities at the time of the missions.